Mental Health Communication in Indonesian Natural Disaster Victims Trauma Recovery - Nani Kurniasari; Satya Candrasari; Santi Delliana (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2021)
Trauma healing is a crucial stage in a long tourism sector recovery process after a natural disaster. Post-disaster psychological support is needed to reduce trauma in society, especially for remote communities. However, health services for people affected by health crises due to disaster at the provincial level are inadequate. This study aims to identify mental health communication forms in the trauma recovery process for tsunami victims in Pandeglang, Banten. This research uses the case study method. Approached descriptive-qualitatively, this study describes the practice of mental health communication in the context of trauma healing for natural disaster victims in Indonesian tourist attractions. This study found that mental health communication efforts included psychosocial assistance for children and adults, treatment for people with mental health disorders (ODGJ- orang dengan gangguan jiwa), counseling for victims, home visits, and health services for 26 ODGJs, and home visits for victims without mental disorders.